A Novel Rat Infant Model of Medial Temporal Lobe Epilepsy Reveals New Insight into the Molecular Biology and Epileptogenesis in the Developing Brain - Carola Wormuth; Anna Papazoglou; Christina Henseler; Dan Ehninger; Karl Broich; Britta Haenisch; Jürgen Hescheler; Rüdiger Köhling; Marco Weiergräber (Neural Plasticity)
Although several adult rat models of medial temporal lobe epilepsy (mTLE) have been described in detail, our knowledge of mTLE epileptogenesis in infant rats is limited. Here, we present a novel infant rat model of mTLE (InfRPil-mTLE) based on a repetitive, triphasic injection regimen consisting of low-dose pilocarpine administrations (180 mg/kg. i.p.) on days 9, 11, and 15 post partum (pp). The model had a survival rate of >80% and exhibited characteristic spontaneous recurrent electrographic seizures (SRES) in both the hippocampus and cortex that persisted into adulthood. Using implantable video-EEG radiotelemetry, we quantified a complex set of seizure parameters that demonstrated the induction of chronic electroencephalographic seizure activity in our InfRPil-mTLE model, which predominated during the dark cycle. We further analyzed selected candidate genes potentially relevant to epileptogenesis using a RT-qPCR approach. Several candidates, such as the low-voltage-activated Ca2+ channel Cav3.2 and the auxiliary subunits β1 and β2, which were previously reported to be upregulated in the hippocampus of the adult pilocarpine mTLE model, were found to be downregulated (together with Cav2.1, Cav2.3, M1, and M3) in the hippocampus and cortex of our InfRPil-mTLE model. From a translational point of view, our model could serve as a blueprint for childhood epileptic disorders and further contribute to antiepileptic drug research and development in the future.